1990
DOI: 10.1113/jphysiol.1990.sp018115
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between quantal secretion and vesicle loss at the frog neuromuscular junction.

Abstract: SUMMARY1. We measured the rate of occurrence of miniature endplate potentials (MEPPs) at identified endplates in frog cutaneus pectoris muscles treated with crude black widow spider venom (BWSV) or purified ac-latrotoxin (a-LTX) in calcium-free solutions, and we examined the relationship between the length of the nerve terminal and the total number of quanta secreted, and the relationship between the number of quanta secreted and the number of vesicles remaining at different times.2. The venom, or toxin, was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…3a, these calcium imaging experiments demonstrate that c~-latrotoxin exerts effects on astrocytes that are similar to the toxin's actions on neurons, c~-latrotoxin stimulates an increase in basal release from neurons in the presence and absence of external calcium ions [25,26]. In the absence of external calcium ions transmitter release is stimulated through a direct induction of exocytosis.…”
Section: I Parpura Et Al/febs Letters 360 (1995) 266 270mentioning
confidence: 65%
See 3 more Smart Citations
“…3a, these calcium imaging experiments demonstrate that c~-latrotoxin exerts effects on astrocytes that are similar to the toxin's actions on neurons, c~-latrotoxin stimulates an increase in basal release from neurons in the presence and absence of external calcium ions [25,26]. In the absence of external calcium ions transmitter release is stimulated through a direct induction of exocytosis.…”
Section: I Parpura Et Al/febs Letters 360 (1995) 266 270mentioning
confidence: 65%
“…In neurons a similar decline in transmitter release has been shown when c~-latrotoxin is applied in calcium-depleted saline. Parallel electron microscopy has indicated that this is due to a depletion of the vesicles in the nerve terminal [25,26]. Similar effects of ~-latrotoxin in neurons and astrocytes raises the possibility that the transmitter release mechanisms of these two cell types share some fundamental properties.…”
Section: I Parpura Et Al/febs Letters 360 (1995) 266 270mentioning
confidence: 98%
See 2 more Smart Citations
“…Upon a-latrotoxin stimulation, the number of neurotransmitter quanta released correlates with the number of synaptic vesicles exocytosed, indicating that toxinstimulated neurotransmitter release occurs via exocytosis [14]. 2.…”
mentioning
confidence: 99%